Characterization and measurement of duration dependence in Hazard rate models - Rolf Aaberge (University of Oslo, Department of Economics, 2002)
As is known from the economic literature, the notion of negative/positive duration dependence defined in terms of a decreasing/increasing hazard function can solely be used as a basis for revealing whether negative/positive duration dependence is present or not. However, when concern is directed to comparison and measurement of the extent of duration dependence in hazard rate models alternative definitions and methods are called for. To this end we propose a stronger as well as a weaker version of the standard definition of duration dependence and demonstrate that these definitions form a useful basis for developing appropriate duration dependence orderings and summary measures of duration dependence.
Keywords: J64; 330; Hazard rate models; duration dependence orderings; summary measures of duration dependence; the Weibull distribution; PH and MPH models; Moral Hazard; Theorie; Statistische Bestandsanalyse